2002
DOI: 10.1148/radiol.2252011605
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Breast Cancer Staging: MR Imaging of the Axilla with Ultrasmall Superparamagnetic Iron Oxide Enhancement

Abstract: USPIO-enhanced MR imaging has the potential to become an adjunct to conventional MR imaging of the breast for preoperative assessment of axillary lymph nodes in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(124 citation statements)
references
References 41 publications
3
118
1
2
Order By: Relevance
“…Its value awaits further evaluation in a large number of cases to conclude whether ADC value measurement of the nodes is helpful in differentiating metastatic from nonmetastatic nodes in breast cancer. USPIO, a lymphographic contrast medium of ironcontaining nanoparticles, has been shown to be useful in the characterization of lymph nodes in neck (7), esophageal (13), gastric (14), prostate (15), bladder (16), and breast cancers (17)(18)(19)(20). After IV injection of USPIO, the nanoparticles circulate systemically and access the interstitium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its value awaits further evaluation in a large number of cases to conclude whether ADC value measurement of the nodes is helpful in differentiating metastatic from nonmetastatic nodes in breast cancer. USPIO, a lymphographic contrast medium of ironcontaining nanoparticles, has been shown to be useful in the characterization of lymph nodes in neck (7), esophageal (13), gastric (14), prostate (15), bladder (16), and breast cancers (17)(18)(19)(20). After IV injection of USPIO, the nanoparticles circulate systemically and access the interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to axillary lymph node staging, there are published data for USPIO-enhanced MRI (17)(18)(19)(20). Researchers in those studies reported a sensitivity of 73%-100% and a specificity of 92%-98% in the nodeby-node evaluation using USPIO.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional MRI demonstrated figures of 59.1, 86.7 and 80.4 % for sensitivity, specificity and overall accuracy, respectively, whereas post-contrast SPIO-enhanced MRI these were 100, 80 and 94 % [25]. In the study by Stadnik et al [28] the sensitivity, specificity, positive and negative predictive values for SPIO-enhanced MRI were recorded at 100, 80, 80 and 100 %, respectively, whilst Michel et al [29] found a sensitivity, specificity and positive predictive value of 82, 100 and 82 %, respectively. These in-vivo and clinical evidence suggests that SPIO-enhanced MRI could prove to be clinically useful as an non-invasive alternative to SLNB.…”
Section: The Role Of Mnps In Diagnosis Of Metastatic Lymph Node Spreadmentioning
confidence: 93%
“…The challenge of applying this model to clinical practice, is the high false positive rate for MRI of 6.3 versus 0.2 % for the current baseline strategy of SLNB. The technique of MRI lymphangiography has not yet been developed sufficiently to achieve the specificity and positive predictive value of SLNB [29].…”
Section: The Future Role Of Mnps In the Management Of The Axilla In Bmentioning
confidence: 99%
“…Despite lots of promising results concerning USPIOenhanced MRI, there are still many important challenges to overcome, in which one problem is false-positive and false-negative results, affecting the accuracy of diagnosis (2,(4)(5)(6)(7)(8)(9)(10)(11)(12). Harisinghani et al (2) reported that there were metastasis nodes that went undetected, and the false diagnosis was not negligible.…”
mentioning
confidence: 99%